Environmental aspects of inter-city passenger transport - Per Kageson (Organisation for Economic Co-operation and Development (OECD), Joint Transport Research Centre (JTRC), 2009)
Many governments in different parts of the world are investing in high speed rail. Some of them do so thinking that it will be an important part of climate change mitigation. Intercity traffic over medium distances is particularly interesting in the environmental context as it constitutes the only transport segment where aircraft, trains, coaches and cars naturally compete for market shares. This report calculates the effect on emissions from building a new high speed link that connects two major cities located 500 km apart. It assumes that emissions from new vehicles and aircraft in 2025 can be used as a proxy for the emissions during a 50 year investment depreciation period. The emissions from the marginal production of electricity, used by rail and electric vehicles, are estimated to amount on average to 530 gram per kWh for the entire period. Fuels used by road vehicles are assumed to be on average 80 percent fossil and 20 per cent renewable (with a 65% carbon efficiency in the latter case). Traffic on the new line after a few years is assumed to consist to 20 per cent of journeys diverted from aviation, 20 per cent diverted from cars, 5 per cent from long-distance coaches, and 30 per cent from pre-existing trains. The remaining 25 per cent is new generated traffic. Under these assumptions would the investment result in a net reduction of CO2-emissions of about 9,000 tons per one million one-way trips. Assuming 10 million single journeys per year, the total reduction would be 90,000 tons. When the price of CO2 is 40 per ton, the socio-economic benefit of the reduction would amount to 3.6 million, which is very little in the context of high speed rail. The sensitivity analysis shows that alternative assumptions do not significantly change the outcome. One may also have to consider the impact on climate change from building the new line. Construction emissions for a line of this length may amount to several million tons of CO2. There is no cause to prohibit investment in high speed rail on environmental grounds so long as the carbon gains made in traffic balances the emissions caused during construction. However, marketing high speed rail as a part of the solution to climate change is clearly wrong. Investment in infrastructure for modal shift should only be considered when traffic volumes are high enough to carry the cost. The principal benefits of high speed rail are time savings, additional capacity and generated traffic, not a reduction of greenhouse gases.
Keywords: 330